When subjects do not agree: A semantic perspective - Mendia, Jon Ander; Espinal, M.Teresa (Proceedings of Sinn und Bedeutung, 2024)
In this paper we examine a number of constructions that show lack of agreement between the subject and either the verb or some constituent within the predicate. We focus on Non-Agreeing Degree constructions (Mendia and Espinal, 2024), which we compare with so- called Pancake Sentences (Enger, 2004; Wechsler, 2011; Haugen and Enger, 2019) and Topic Categorical Sentences (Britto, 2000). All three constructions show a non-standard agreement pattern that nevertheless signals some form of semantic shift in interpretation. We argue that, despite surface similarities, these constructions do not belong to the same category.